PRODUKSI MALTODEKSTRIN DARI TEPUNG SAGU MENGGUNAKAN ENZIM Α-AMILASE - Sunari Sunari; Syaiful Bahri; Hardi Ys. (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
The title of this research is “ the production of maltodextrin of sagoo flour using α-amylase”. The objective of this research is to find out the amount of sagoo flour, enzym and time reaction the produced maltodextrin with the highest dextrosa equivalent. To find the highest dextrosa equivalent, the treatment was vary the weight of sagoo flour, the amount of enzym and time. The variation of sagoo flour weight was 6, 8, 10, 12 and 14 gram. The variation of enzym is 0.1, 0.11, 0.12, 0.13, and 0.14 mL. The variation of time was 70, 80, 90, 120, 150, 180 and 210 minutes. The results of this research showed the best sagoo flour is 8 gr with de amount is 11,835, and the best omount of enzym is 0,14 mL with de amount 21.71, the best time reaction is 120 minutes with de amount is 17.625Keywords: sagoo flour, enzym α-amylase, maltodextrin